DEVELOPMENT OF PET CHEWS UTILIZING PIG EAR LOBES BY SUN DRYING METHOD - munagala, yaswanth reddy; Sudheer, K.; Reddy, G. V. Bhaskar; Venkateswarlu, S.; Naveen , Z. (Journal of Meat Science, 2023)
The slaughter of pig is mainly done for its meat and offal’s, along with there is generation of other by-products like ears, feet, lard, blood, bones etc. The present work was designed in order to utilize the pig ear lobes as dried pet chews by using sun drying method which serves as feed stuff for pet animals. In sun drying method the results revealed significant (P<0.05) differences for treatment samples when compared to control sample for all the parameters studied, except for crude protein, ether extract and overall acceptability which was insignificant. Texture profile analysis revealed significant (P<0.05) differences among all the samples for hardness, springiness, cohesiveness and chewiness. However, sensory evaluation results revealed high scores for the sample which was sun dried for 4 days (T5) when compared with the other treatments.